Measuring the impacts of agriculture projects on good job creation in Central and West Asia Implications for economic analysis - Quilloy, Antonio Jesus A. (Journal of Economics, Management & Agricultural Development, 2019)
Using a simple labor market model, this paper demonstrated how the impacts of agriculture projects on the creation of good jobs in the agriculture sector can be estimated. By applying the model to the case of Tajikistan’s agriculture, the study found that agriculture projects which promote crop diversity, market connectivity, and agricultural exports have high potential for contributing to the creation of good jobs in the country’s agriculture sector. This paper further underscored the relevance of using the good job creation potential as an appropriate indicator for evaluating the economic viability of agricultural projects.